Marcos Saquet. Saber popular, práxis territorial e contra-hegemonia - Luiz Carlos Flávio (Perspectiva Geográfica, 2021)
Saquet, M. (2019). Saber popular, práxis territorial e contra-hegemonia. Editora Consequência, 141 pp. ISBN: 9788569437628.